Self-Reported Perceptions of Preparedness among Incoming Ophthalmology Residents - Lin, Benjamin R.; Nguyen, Geoffrey; Sridhar, Jayanth; Cavuoto, Kara (Journal of Academic Ophthalmology, 2023)
Purpose The purpose of this study was to assess the self-perceived preparedness of incoming postgraduate year 1 (PGY1) and postgraduate year 2 (PGY2) ophthalmology interns/residents to carry out core competencies in ophthalmology.Methods An online survey was created using the Survey Monkey survey platform and distributed to all ophthalmology resident applicants to the Bascom Palmer Eye Institute from the 2021 to 2022 and 2022 to 2023 application cycles. The survey contained questions pertaining to demographics, prior ophthalmic experience, online resources that were used to prepare for ophthalmology, and self-perceived preparedness to carry out key clinical skills in ophthalmology.Results A total of 170 responses were obtained (16.1% response rate). Of those, 119 (70%) were incoming PGY1 interns and 51 (30%) were incoming PGY2 residents for the 2022 to 2023 academic year. Most respondents (90.6%, n = 154) reported that their ophthalmology residency was affiliated with an integrated ophthalmology intern year. Incoming PGY2s moderately agreed with the statement that they felt as prepared to see patients in ophthalmology as they do in other surgical subspecialties, whereas incoming PGY1s only mildly agreed with that statement (p = 0.003). Both incoming PGY1s and PGY2s felt most prepared to obtain histories relating to basic ophthalmic complaints and felt least prepared to read and interpret ophthalmic imaging studies. The most popular online resources used by respondents in order of popularity were EyeGuru (35.2%, n = 60), EyeWiki (32.9%, n = 56), Tim Root/OphthoBook (26.5%, n = 45), American Academy of Ophthalmology (13.5%, n = 23), and EyeRounds/University of Iowa (13.5%, n = 23).Conclusion A major challenge in integrating ophthalmic education into the medical school curricula is the gradual shift toward shorter preclinical curricula. However, having a core foundation of ophthalmic knowledge is critical for incoming ophthalmology residents to be able to maximize their specialty-specific training. Integrated ophthalmology intern years likely play a significant role in the increased self-efficacy of incoming PGY2s compared with incoming PGY1s. Adopting nontraditional teaching methods like flipped classroom learning, utilizing online medical education resources, and continuing to increase ophthalmology exposure during PGY1 year may better prepare incoming PGY2s to operate independently in ophthalmology settings.
Keywords: preparedness; ophthalmology intern year; online education; self-assessment; self-assessed; self-reported